Eight new Halophytophthora species from marine and brackish-water ecosystems in Portugal and an updated phylogeny for the genus - Maia, C; Horta Jung, M; Carella, G; Milenković, H K; Janoušek, J; Tomšovský, M; Mosca, S; Schena, L; Cravador, A; Moricca, S; Jung, T (Persoonia, 2022)
During an oomycete survey in December 2015, 10 previously unknown Halophytophthora taxa were isolated from marine and brackish water of tidal ponds and channels in saltmarshes, lagoon ecosystems and river estuaries at seven sites along the Algarve coast in the South of Portugal. Phylogenetic analyses of LSU and ITS datasets, comprising all described Halophytophthora species, the 10 new Halophytophthora taxa and all relevant and distinctive sequences available from GenBank, provided an updated phylogeny of the genus Halophytophthora s.str. showing for the first time a structure of 10 clades designated as Clades 1-10. Nine of the 10 new Halophytophthora taxa resided in Clade 6 together with H. polymorphica and H. vesicula. Based on differences in morphology and temperature-growth relations and a multigene (LSU, ITS, Btub, hsp90, rpl10, tigA, cox1, nadh1, rps10) phylo-geny, eight new Halophytophthora taxa from Portugal are described here as H. brevisporangia, H. cele-ris, H. frigida, H. lateralis, H. lusitanica, H. macrosporangia, H. sinuata and H. thermoambigua. Three species, H. frigida, H. macrosporangia and H. sinuata, have a homothallic breeding system while the remaining five species are sterile. Pathogenicity and litter decomposition tests are underway to clarify their pathological and ecological role in the marine and brackish-water ecosystems. More oomycete surveys in yet undersurveyed regions of the world and population genetic or phylogenomic analyses of global populations are needed to clarify the origin of the new Halophytophthora species. Citation: Maia C, Horta Jung M, Carella G, et al. 2022. Eight new Halophytophthora species from marine and brackish-water ecosystems in Portugal and an updated phylogeny for the genus. Persoonia 48: 54 - 90. https://doi.org/10.3767/persoonia.2022.48.02..
Keywords: lifestyle; oomycetes; Peronosporaceae; breeding system; evolution; ecological role; Phytophthora